Radiation threats and your safety : a guide to preparation and response for professionals and community - Ansari, Armin (CRC Press, 2010)
Details protocols for accidental and intentional emergencies such as nuclear explosions and dirty bombs. This book shows how to prepare a family emergency plan, covers medical responses to radiation including radiation drugs, and discusses radiation from microwaves and cellular phones as well as food irradiation.